BENTUK, PENEMPATAN DAN MAKNA MOTIF UKIRAN BAGAS GODANG DI DESA HUTA GODANG KABUPATEN MADINA SUMUT - Fatimah Siregar; Efrizal .; Eliya Pebriyeni (Serupa The Journal of Art Education, 2012)
Abstrak The purpose of this study was to determine the shape, placement and meaning carving motifs used in Bagas Godang Huta district Godang Mandailing Natal. The data source is data collected using interviews and documentation. The findings of the study. (1) sun carving placed above the entrance Bagas Godang meaning as enlightening the people, (2) carving ulok (snake) placed in front of the statue of the music room Bagas Godang, (3) engraving podang (sword) was placed on the wall of the music room terrace Bagas Godang, meaning truth and power of the king, (4) pit carved nihorbo (buffalo head, placed on the wall of the music room terrace Bagas Godang, (5) carving siadop-adop (face to face) is placed on a slab patio Godang meaning Bagas protect each other, (6) carving pusuk nirobung (shoots shoots) were placed on a slab patio Bagas Godang, meaning custom Dalihan natolu, (7) carving shrimp placed on a slab patio Botik Bagas Godang, meaning the king's relationship with the community is very closely. Kata kunci: bentuk, penempatan, makna, motif ukiran, Bagas Godang